(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Epilepsy patients are usually managed medically but some cases are resistant to medical treatment and needs surgical treatment. Temporal lobe epilepsy (TLE) is commonly intractable. The underlying cause may be mesial temporal sclerosis(MTS), cortical dysplasia(CD), tumors (ganglioglioma, dysembryoplastic neuroepithelial tumor- DNET), post traumatic gliosis, infection (tuberculosis) parasitic infestation (schistosomiasis, neurocystocercosis) etc. In this type of epilepsy surgery is the treatment of choice (even there is no symptoms other than seizure). Here we report two cases of surgically treated TLE that were due to low grade ganglioglioma and high grade ganglioglioma. In both cases the only presenting symptoms was complex partial seizure (Psychomotor epilepsy) for which they underwent scalp EEG (Electro Encephalography) and MRI (Magnetic Resonance Imaging) of brain. Both patients were managed by complete tumor excision with amygdalohippocampectomy plus standard anterior lobectomy. One patient with high grade ganglioglioma recurred within two months of operation and expired within five months. The other case was seizure and disease free till last follow up. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21007 J Bangladesh Coll Phys Surg 2013; 31: 214-218